Characterization of ZnO Nanoparticles Prepared in Curcuma Aromatica Salisb. Root Extract - Abdul Kareem Thottoli; Ameera P.I.; Ajitha P.; Vrinda C.; Karamunnisa K.; Thamanna Shaharbanu M.H.; Sajna T.P.; Arshadha K.T.; Islam M Al-Akraa; Ahmad M. Mohammad; Chandramohan S. (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2022)
The root extract of the locally available Curcuma Aromatica Salisb. was used with the ZnO precursors to study the effect of the Curcuma Aromatica Salisb.  extract on the growth and optical absorption behaviour of the ZnO nanoparticles. ZnO nanoparticles were synthesized in various concentrations of Curcuma Aromatica Salisb. root extract. X-ray diffraction studies show that the prepared samples consist of nanocrystallites of having sizes in the range between 17 nm to 26 nm. The optical absorption studies reveal that the eco-dying on ZnO nanoparticles using Curcuma Aromatica Salisb. root extract has enhanced the optical absorption behaviour of ZnO to the visible region of the spectrum.